High Efficiency Perovskite Solar Cells Employing Quasi‐2D Ruddlesden‐Popper/Dion‐Jacobson Heterojunctions. (15th February 2022) - Li, Kang; Yue, Shengli; Li, Xing; Ahmad, Nafees; Cheng, Qian; Wang, Boxin; Zhang, Xuning; Li, Shilin; Li, Yanxun; Huang, Gaosheng; Kang, Hui; Yue, Tong; et al.
Abstract: While 2D Ruddlesden‐Popper (RP) perovskites exhibit attractive opto‐electronic properties and stability for use in perovskite solar cells (PSCs), their complicated film‐forming processes often induce a non‐negligible level of defects that significantly undermine the power conversion efficiency (PCE) and stability of PSCs. Here, the use of two organic ammonium salts with the same chain length, namely monoammonium (butylammonium iodide, BAI) and diammonium (1, 4‐butanediamine dihydroiodide, BDAI2 ) for surface defect passivation of RP‐2D perovskite films of (AA)2 MA4 Pb5 I16 ( n  = 5) are reported. It is found that the diammonium BDAI2 not only effectively reduces the defect density (similarly to using monoammonium BAI) but forms a Dion‐Jacobson (DJ) 2D structure to enhance interfacial charge extraction and suppress surface charge recombination. As a result, a boosted PCE of 18.34% has been obtained with a high open‐circuit voltage of 1.24 V. Owing to the enhanced structural integrity of the DJ phase, the RP‐2D/DJ‐2D perovskite heterojunction films exhibit supreme material robustness, which translates to the impressive environmental stability of devices, showing nearly zero‐degradation of the efficiency after 800 h of continuous thermal aging (60 °C) for 800 h. This work enriches the fundamental understanding of the impacts of the DJ‐2D structure on the surface properties of 2D perovskites. Abstract : 1, 4‐Butanediamine dihydroiodide not only effectively reduces the defect density but forms a Dion‐Jacobson 2D structure to enhance interfacial charge extraction and suppresses surface charge recombination, leading to a nearly zero‐degradation of the efficiency after 800 h of continuous thermal aging (60 °C) with a high open‐circuit voltage of 1.24 V and power conversion efficiency of 18.34%.